TANGGUNG JAWAB PENDIDIK DAN PESERTA DIDIK DALAM MENEGAKKAN KEWAJIBAN BERILMU PERSPEKTIF HADIS - Abdurrahim Albukhori; Aida Rumaratu (Sekolah Tinggi Ilmu Al-Qur'an (STIQ) Ar-Rahman, 2025)
This study examines in depth the responsibilities of educators and students in the perspective of the hadith narrated by Abdullah bin Amr bin Al-Ash, which explains that the loss of knowledge can occur not because it is directly revoked, but because of the death of scholars, causing society to lose a source of authentic law. The weakening of commitment, morals, and manners is a major problem in this study, which has an impact on the decline in the quality of knowledge in Islamic education. This study aims to analyze the meaning of the obligation to learn and teach as a mandate that must be upheld by both parties so that knowledge can maintain its blessings and authority. The method used is a qualitative method through a literature study by examining hadith, classical literature, and contemporary research. The results of the study show that educators have the responsibility to convey knowledge correctly, honestly, and to be role models, while students are responsible for seeking knowledge earnestly, maintaining manners, and practicing knowledge consistently. Further analysis reveals that negligence on the part of either party can lead to the emergence of uneducated leaders who give guidance without a valid basis or law.